2016
DOI: 10.1111/ijcp.12909
|View full text |Cite
|
Sign up to set email alerts
|

Perception of prognosis of cancer patients by non-oncologists

Abstract: Non-oncologists are considerably over pessimistic regarding their perception of the cancer patients' prognosis. A pessimistic perception of prognosis might cause undertreatment and therefore affect both patients' quality of life and their actual survival. Education regarding cancer therapy and its benefits should be emphasised for non-oncologists involved in cancer patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…These findings were reproduced in a subsequent study in which the physician’s prognosis discrepancy increased toward more pessimistic predictions when patients had a diagnosis for illnesses other than cancer such as AIDS, chronic heart failure, or stroke. 55 Likewise, a third study 62 showed that a higher proportion of physicians had pessimistic perceptions of prognosis for malignancies with high cure rates sparking from long-standing achievements of medical research, compared with malignancies with similar cure rates but whose data were derived from more recent research advancements. Furthermore, physicians gave more optimist prognostic estimates for patients with chronic myelogenic leukemia than for patients with acute leukemia and non-Hodgkin lymphomas.…”
Section: Resultsmentioning
confidence: 99%
“…These findings were reproduced in a subsequent study in which the physician’s prognosis discrepancy increased toward more pessimistic predictions when patients had a diagnosis for illnesses other than cancer such as AIDS, chronic heart failure, or stroke. 55 Likewise, a third study 62 showed that a higher proportion of physicians had pessimistic perceptions of prognosis for malignancies with high cure rates sparking from long-standing achievements of medical research, compared with malignancies with similar cure rates but whose data were derived from more recent research advancements. Furthermore, physicians gave more optimist prognostic estimates for patients with chronic myelogenic leukemia than for patients with acute leukemia and non-Hodgkin lymphomas.…”
Section: Resultsmentioning
confidence: 99%
“…As a bibliometric experiment, I made a list of all EC articles from 2016 to 2017, excluding editorials, and examined the number of downloads from the journal's website ascertained by Wiley as of 22 August 2018 (Table ). For the articles published in 2016 and 2017, I also compiled a list of the top 10 downloaded articles from the journal (Table ).…”
Section: Articles From the International Journal Of Clinical Practicementioning
confidence: 94%
“…Cancer stigma is caused by the ability of cancer cells to metastasize and replicate without control and the side effects of therapy which significantly affect physical function disorders. The health team is also pessimistic about the prognosis of cancer, especially if the patient is found at an end-stage [2]. Other people's opinions of cancer can affect the patient's self-concept dimensions.…”
Section: Introductionmentioning
confidence: 99%